Rapid Simultaneous Determination of 43 Pesticide Residues in Schizonepeta tenuifolia by Gas Chromatography Mass Spectrometry. (13th December 2021) - Zhou, Guo-wei; Li, Yong-mei; Liu, Chun-ni; Ren, Hong-min; Li, Hai-ying
Abstract : A simple, fast, and reliable method was established for simultaneous determination of 43 pesticides in Schizonepeta tenuifolia . The samples were prepared using solid-phase extraction (SPE) method. Pesticides were extracted from Schizonepeta tenuifolia using acetonitrile, cleaned with Pesticarb/NH2, and eluted by mixed solvents of acetonitrile and toluene (3 : 1, v/v). Selected pesticides were identified using DB-35MS capillary column and detected by gas chromatography mass spectrometry. Samples were quantified by external standard method. Recoveries for the majority of pesticides at spike levels of 0.2, 0.5, and 1 mg kg −1 ranged between 70 and 120% (except for Chlorothalonil, Thiamethoxam, and Dicofol), and the relative standard deviations (RSDs n  = 6) were 1.32%–13.91%. Limits of detection (LODs) were 0.0011–0.0135 mg kg −1, whereas limits of quantification (LOQs) were 0.0038–0.0451 mg kg −1 . The satisfactory accuracy and precision, in combination with a good separation and few interferences, have demonstrated the strong potential of this technique for its application in Schizonepeta tenuifolia analysis.